2011
DOI: 10.1589/jpts.23.713
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Balance Training with Various Dual-Task Conditions on Stroke Patients

Abstract: The aim of this study was to determine the effects of motor dual-task training (MDT), cognitive dual-task training (CDT), and motor and cognitive dual-task training (MCDT) on balance and daily living abilities of stroke patients. In addition, the relationships among assessment tools such as center of pressure (COP), Korean version of Berg Balance Scale (K-BBS), and the Functional Independence Measure (FIM) were investigated. [Subjects and Method] Thirty-eight stroke patients were randomly allocated to a MDT gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 21 publications
5
21
0
Order By: Relevance
“…These findings are consistent with other studies in which the average values were better in dual-task training programs, but with no significant results (Vaillant et al 2006;Her et al 2011;Jiejiao et al 2012;Plummer-D'Amato et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with other studies in which the average values were better in dual-task training programs, but with no significant results (Vaillant et al 2006;Her et al 2011;Jiejiao et al 2012;Plummer-D'Amato et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…This result is similar to that in the study of Her et al13 ) which showed significant improvement in the BBS score after training in VDT, UDT, and VUDT groups. Improved BBS score indicates improvement of a stroke patient’s balance ability, as it tests balance ability within many different tasks.…”
Section: Discussionsupporting
confidence: 91%
“…The COP moving distance decreased the most in the VUDT group. This result corresponded with the findings from previous studies where persons affected by stroke showed decreased sway after undergoing dual-task training [13,15]. Swan et al [15] reported that postures with a high level of difficulty increase signals related to postural balance in various organs.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to the types of research described above, few studies have been conducted on the balance and concentration abilities in persons with stroke with consideration of both visual restriction and base conditions related to a person's postural control ability. To increase the effects of dual-task training, visual effects [13] and base effects [14] should both be considered. In this regard, we conducted a study where persons with stroke performed dual-task training under visual restriction and unstable base conditions to examine changes in their balance and concentration ability and provide references that can help establish interventions to improve the balance and attention abilities in persons with stroke.…”
Section: Introductionmentioning
confidence: 99%